Extent of late gadolinium enhancement predicts thromboembolic events in patients with hypertrophic cardiomyopathy - Hohneck, Anna; Overhoff, Daniel; Dösch, Christina; Rudic, Boris; Tueluemen, Erol; Budjan, Johannes; Szabo, Kristina; Borggrefe, Martin; Papavassiliu, Theano (Circulation journal, 2020)
Background: Thromboembolic complications such as ischemic stroke or peripheral arterial thromboembolism are known complications in hypertrophic cardiomyopathy (HCM). We sought to assess the clinical and cardiovascular magnetic resonance (CMR) characteristics of patients with HCM suffering from thromboembolic events and analyzed the predictors of these unfavorable outcomes. Methods and Results: The 115 HCM patients underwent late gadolinium enhanced (LGE) CMR and were included in the study. Follow-up was 5.6 +/- 3.6 years. The primary endpoint was the occurrence of thromboembolic events (ischemic stroke or peripheral arterial thromboembolism). It occurred in 17 (14.8%) patients (event group, EG), of whom 64.7% (11) were men. During follow-up, 10 (8.7%) patients died. Patients in the EG showed more comorbidities, such as heart failure (EG 41.2% vs. NEG (non-event group) 14.3%, P<0.01) and atrial fibrillation (AF: EG 70.6% vs. NEG 36.7%, P<0.01). Left atrial end-diastolic volume was significantly higher in the EG (EG 73 +/- 24 vs. NEG 50 +/- 33 mL/m(2), P<0.01). Both the presence and extent of LGE were enhanced in the EG (extent% EG 23 +/- 15% vs. NEG 8 +/- 9%, P<0.0001). No patient without LGE experienced a thromboembolic event. Multivariate analysis revealed AF and LGE extent as independent predictors. Conclusions: LGE extent (>14.4%) is an independent predictor for thromboembolic complications in patients with HCM and might therefore be considered as an important risk marker. The risk for thromboembolic events is significantly elevated if accompanied by AF.
Gesehen am 03.06.2020